Flip-Flopping Retinal in Microbial Rhodopsins as a Template for a Farnesyl/Prenyl Flip-Flop Model in Eukaryote GPCRs - De Loof, Arnold; Schoofs, Liliane (Frontiers in Neuroscience, 2019)
Thirty years after the first description and modeling of G protein coupled receptors (GPCRs), information about their mode of action is still limited. One of the questions that is hard to answer is: how do the allosteric changes in the GPCR induced by e.g. ligand binding in the end activate a G protein-dependent intracellular pathway (e.g. via the cAMP or the phosphatidylinositol signal pathways). Another question relates to the role of prenylation of G proteins. Today’s “consensus model” states that protein prenylation is required for the assembly of GPCR-G protein complexes. Although it is well known that protein prenylation is the covalent addition of a farnesyl- or geranylgeranyl moiety to the C terminus of specific proteins, e.g. α or γ G protein, the reason for this strong covalent binding remains enigmatic. The arguments for a fundamental role for prenylation of G proteins other than just being a hydrophobic linker, are gradually accumulating. We uncovered a dilemma that at first glance may be considered physiologically irrelevant, however, it may cause a true change in paradigm. The consensus model suggests that the only functional role of prenylation is to link the G protein to the receptor. Does the isoprenoid nature of the prenyl group and its exact site of attachment somehow matter? Or, are there valid arguments favouring the alternative possibility that a key role of the G protein is to guide the covalently attached prenyl group to - and it hold it in – a very specific location in between specific helices of the receptor? Our model says that the farnesyl/prenyl group - aided by its covalent attachment to a G protein -might function in GPCRs as a horseshoe-shaped flexible, (and perhaps flip-flopping) hydrophobic valve for restricting (though not fully inhibiting) the untimely passage of Ca2+, like retinal does for the passage of H+ in microbial rhodopsins that are ancestral to many GPCRs.